Computational Thinking in Mathematics Education : A Systematic Literature Review on its Implementation and Impact on Students' Learning - Fauzi, Ahmad Lutfi; Kusumah, Y S; Nurlaelah, Elah; Juandi, Dadang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to analyze the impact of mathematics learning using Computational Thinking (CT) integration and to enlighten educators, researchers, and policy makers on the tactics, benefits, and challenges involved in incorporating CT into mathematics education by synthesizing existing research and educational initiatives. Using the systematic literature review (SLR) method with a qualitative approach, the results of this research were in the form of descriptive analysis. The database used was Scopus to filter relevant material about CT and mathematics education. Based on the search, nine publications from 2019 – 2023 were selected systematically based on the PRISMA protocol. This study's results indicated a relationship between CT and several students' mathematical abilities, such as problem-solving and improving problem-solving skills. Not only can it improve the cognitive side of students, but CT can also improve students' affective side, such as increasing creativity, confidence, and involvement in the learning process. The impact felt is not only in the micro scope (in the classroom), but can also be macro. CT can improve the quality of higher learning, so CT research can be used to determine a country's curriculum.